2015
DOI: 10.1371/journal.pone.0116658
|View full text |Cite
|
Sign up to set email alerts
|

Relative Sensitivity of Conventional and Real-Time PCR Assays for Detection of SFG Rickettsia in Blood and Tissue Samples from Laboratory Animals

Abstract: Studies on the natural transmission cycles of zoonotic pathogens and the reservoir competence of vertebrate hosts require methods for reliable diagnosis of infection in wild and laboratory animals. Several PCR-based applications have been developed for detection of infections caused by Spotted Fever group Rickettsia spp. in a variety of animal tissues. These assays are being widely used by researchers, but they differ in their sensitivity and reliability. We compared the sensitivity of five previously publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…In a previous study, the sensitivity of 4 cPCR protocols based on ompB, rpoB, gltA and hrtA genes and 1 SYBR Greenbased qPCR assay were compared for the detection of rickettsial DNA in blood and tissue samples from Rickettsia-infected laboratory animals (n = 87). While rickettsial DNA was detected in 39.1% of samples by qPCR, cPCR assays detected Rickettsia DNA in 14.9% of samples (Zemtsova et al, 2015). The results of the present study corroborate those found by Zemtsova et al (2015) that showed that qPCR assays show a higher sensitivity when compared to more traditional assays in detecting rickettsial DNA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a previous study, the sensitivity of 4 cPCR protocols based on ompB, rpoB, gltA and hrtA genes and 1 SYBR Greenbased qPCR assay were compared for the detection of rickettsial DNA in blood and tissue samples from Rickettsia-infected laboratory animals (n = 87). While rickettsial DNA was detected in 39.1% of samples by qPCR, cPCR assays detected Rickettsia DNA in 14.9% of samples (Zemtsova et al, 2015). The results of the present study corroborate those found by Zemtsova et al (2015) that showed that qPCR assays show a higher sensitivity when compared to more traditional assays in detecting rickettsial DNA.…”
Section: Discussionsupporting
confidence: 87%
“…While rickettsial DNA was detected in 39.1% of samples by qPCR, cPCR assays detected Rickettsia DNA in 14.9% of samples (Zemtsova et al, 2015). The results of the present study corroborate those found by Zemtsova et al (2015) that showed that qPCR assays show a higher sensitivity when compared to more traditional assays in detecting rickettsial DNA.…”
Section: Discussionsupporting
confidence: 87%
“…DNA extraction and qPCR procedures were carried out in separate facilities as described (Levin et al 2012, Zemtsova et al 2015). DNA was extracted from ticks and blood samples using the Qiagen DNEasy Blood and Tissue kit (Qiagen Inc., Valencia, CA) according to manufacturer’s protocols.…”
Section: Methodsmentioning
confidence: 99%
“…There were eight instances across the 111 isolates of genes being identified by the HRM assay that were not identified by the reference standard. The reference tests used were well characterized standard PCRs relying on gel based detection, which can be less sensitive than real-time methods 49 and therefore it is possible that these were truly positive isolates. The specificity of HRM assays are typically very high, as they rely on both the specificity of the primer pairs, and the melt temperature of the amplicon generated.…”
Section: Discussionmentioning
confidence: 99%